PENGARUH KOMPOSISI KOTORAN JANGKRIK DAN 3 JENIS TANAH YANG BERBEDA TERHADAP PERTUMBUHAN SEMAI SENGON LAUT SAMPAI UMUR 3 BULAN - , PROBO SANTOSO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the successful key of planting on field is the quality of seedling that going to plant. To produce a qualited seedling it needs perfect composition of media that has great porosity, aeration, and drainage. Thatâs why some materials to mix media that use is needed to find. This research made to find the impact of composition of crickets dirt and regosol soil, rendzina soil, and latosol soil for the growth of seedling sengonlaut(P. falcataria). This research use CRD (Completely Randomized Design) with 3 kind of soil and 1 organic material and control. Every treatment use 4 seedling and repeated 3 times. Characters that counts is the height, diametre, and percentage of life. The result of the research shows that dirt crickets given 3 different kind of soils doesnât show any real impact to the seedling growth of sengonlaut, but seedling that plant on an mixture of dirt crickets media can survive till the end of observation. Control life percentage 100% and the height growth of seedling is 8,7 cm in regosol soil, 8,3 cm for rendzina soil, and 7,8 for latosol soil.